Comparative effectiveness of novel oral anticoagulants in UK patients with non-valvular atrial fibrillation and chronic kidney disease: a matched cohort study. Issue 1 (24th January 2018) - Loo, Simone Y; Coulombe, Janie; Dell'Aniello, Sophie; Brophy, James M; Suissa, Samy; Renoux, Christel
Abstract : Objectives: To evaluate the effectiveness and safety of novel oral anticoagulants (NOACs) compared with vitamin K antagonists (VKAs) among patients with non-valvular atrial fibrillation (NVAF), particularly those with chronic kidney disease (CKD). Design: Population-based matched cohort study. Setting: Over 670 primary care practices in the UK, contributing to the Clinical Practice Research Datalink. Participants: Up to 6818 adult patients newly treated with NOACs between 2011 and 2016, matched 1:1 to new users of VKAs on age, sex and high-dimensional propensity score. Interventions: Current exposure to NOACs compared with current exposure to VKAs. Main outcome measures: HRs of ischaemic stroke and systemic embolism (SE), major bleeding, gastrointestinal (GI) bleeding, intracranial bleeding, myocardial infarction and all-cause mortality. Results: In as-treated analyses, the rates of ischaemic stroke/SE were similar between NOACs and VKAs (HR 0.94; 95% CI 0.62 to 1.42), as were the rates of major bleeding (HR 0.86; 95% CI 0.56 to 1.33). NOACs also significantly increased the risk of GI bleeding (HR 1.78; 95% CI 1.27 to 2.48). In patients with NVAF and CKD, NOACs and VKAs remained comparable with respect to the risk of ischaemic stroke/SE (HR 0.79; 95% CI 0.40 to 1.58) and major bleeding (HR 0.88; 95% CI 0.47 to 1.62), with no difference in the risk of GI bleeding (HR 0.99; 95% CI 0.63 to 1.55). Similar results were obtained in on-treatment analyses using a time-dependent exposure definition. Conclusions: Our results suggest that in the UK primary care, NOACs are overall effective and safe alternatives to VKAs, among patients with NVAF altogether, as well as in patients with NVAF and CKD.